(untitled) (The International Journal for Scientific Research, 2024)
The study aimed to investigate the use of artificial intelligence techniques to enhance decision-making processes in administrative decisions and promote innovation in Saudi economic institutions, in addition to understanding how to effectively apply artificial intelligence techniques in a business context. The researcher adopted a descriptive-analytical approach in this study, utilizing a survey tool for data collection. The research community represented all individuals working within the Saudi economic institutions sector, and the study sample consisted of 80 employees. The study reached several theoretical and practical results, the most important of which are: - Artificial intelligence represents one of the pillars of economic progress, manifested in the quality of decision-making within Saudi economic institutions. - The efficiency of administrative decisions is influenced by the extent of their application of artificial intelligence techniques at all management levels within Saudi economic institutions. - Artificial intelligence techniques enhance innovation levels within Saudi economic institutions." The study recommended several recommendations, the most prominent of which are: Investing in artificial intelligence technologies and activating their application within Saudi economic institutions, relying on artificial intelligence techniques in designing the policies of Saudi economic institutions at all administrative levels and implementing their decisions, applying the use of artificial intelligence techniques in finding suitable alternatives to design new strategies to create opportunities for innovation and development within Saudi economic institutions.